Pengaruh model artikulasi dan role playing terhadap hasil belajar bahasa indonesia - Amelia Putri; Supriadi; Erwin Nurdiansyah (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This study aims to determine the effect of applying the cooperative learning model of the Articulation type and the Role Playing model assisted by animated videos on the creativity and learning outcomes of fifth-grade students at SDN 239 Inpres Nipa, Maros Regency. The background of this research arises from the low level of student participation and learning outcomes due to the dominance of lecture-based methods and the lack of creative learning media. The study employed a quantitative approach with a one-group pretest-posttest design. The subjects were fifth-grade students of SDN 239 Inpres Nipa. Data were collected through teacher and student activity observations, learning outcome tests, and creativity questionnaires. Data analysis was carried out descriptively and inferentially to determine the improvement in learning outcomes before and after the implementation of the learning models. The results showed that the application of the cooperative learning model of the Articulation type and the Role Playing model assisted by animated videos significantly improved students’ creativity and learning outcomes. This model proved effective in actively engaging students, fostering communication, and creating an enjoyable and meaningful learning atmosphere.